Primary School Education May Be Sufficient to Moderate a Memory-Hippocampal Relationship - Resende, Elisa de Paula França; Rosen, Howard J.; Chiang, Kevin; Staffaroni, Adam M.; Allen, Isabel; Grinberg, Lea T.; Carmona, Karoline Carvalho; Guimarães, Henrique Cerqueira; Carvalho, Viviane Amaral; Barbosa, Maira Tonidandel; de Souza, Leonardo Cruz; Caramelli, Paulo (Frontiers in Aging Neuroscience, 2018)
According to the cognitive reserve theory, intellectual stimuli acquired during life can prevent against developing cognitive impairment. The underlying cognitive-reserve mechanisms were underexplored in low-educated individuals. Because episodic memory impairment due to hippocampal dysfunction is a key feature of Alzheimer’s dementia, we sought to look at a possible cognitive reserve mechanism by determining whether few years of education moderated the relationship between the hippocampal volumes and the episodic-memory scores. The sample was composed by 183 older adults, 40.1% male, with the median age of 78[76,82]years and the median years of education of 4[2,10] who had undergone an episodic-memory test and a 3-Tesla MRI scan to access the hippocampal volumes. Overall, 112 were cognitively healthy, 26 had cognitive impairment-no dementia and 45 had dementia. We used multiple linear regression to assess whether the interaction between years of education and each hippocampal volume significantly predicted the episodic-memory scores’ variance, controlling for cognitive diagnosis and nuisance variables. The interaction term with the left hippocampus (ß=0.2, p=0.043, CI=1.0,1.4), but not with the right (ß=0.1, p=0.218, CI=0.9,1.2) significantly predicted the variation on memory scores. The mechanism by which the left hippocampus seems to play a more important role on memory processing in more educated individuals needs to be further investigated and might be associated with a better use of mnemonic strategies or higher hippocampal connectivity. Because the sample’s median years of education was four, which corresponds to primary school, we may infer that this level might be sufficient to contribute for building cognitive reserve.